1996
DOI: 10.1007/bf00262811
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of skeletal muscle hypertrophy in rats: the testosterone to cortisol ratio

Abstract: This study determined the influence that the catabolic hormone, corticosterone (C), and the anabolic hormone, testosterone (T), had in regulating skeletal muscle hypertrophy using the rat hind limb ablation model. Specifically, the ratio of T:C (TCR) was manipulated via hormone implants and injections and concentrations measured to evaluate the relative contribution of each hormone to skeletal muscle protein balance. Skeletal muscle growth was measured 16 days after gastrocnemius muscle ablation. Elevations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 29 publications
2
25
0
6
Order By: Relevance
“…However, some trend towards a negative relationship with cortisol and a positive relationship with the T:C ratio should be noted. This may re¯ect the hormonal regulation of muscle hypertrophy that has been described in animals (Crowley and Matt 1996) and observed in younger men (Busso et al 1990). The T:C ratio and DHEAS:C ratio have been proposed to be useful indicators of anabolic/catabolic balance (Busso et al 1990;Morales et al 1998).…”
Section: Discussionmentioning
confidence: 93%
“…However, some trend towards a negative relationship with cortisol and a positive relationship with the T:C ratio should be noted. This may re¯ect the hormonal regulation of muscle hypertrophy that has been described in animals (Crowley and Matt 1996) and observed in younger men (Busso et al 1990). The T:C ratio and DHEAS:C ratio have been proposed to be useful indicators of anabolic/catabolic balance (Busso et al 1990;Morales et al 1998).…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, anabolic hormones such as T and hGH, have been associated with enhanced synthesis of muscle protein leading to hypertrophy (Crowley and Matt 1996). It has been shown that concurrent strength and endurance training can elevate post-exercise serum cortisol concentration (Kraemer et al 1995) and resting UC concentrations (Bell et al 1997).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, others did not observe an increase in testosterone [2,12,31] and hGH concentrations [12,32] after resistance exercise. Cortisol concentrations, which suppresses protein synthesis [3,24], do not appear to be altered with resistance exercise in elderly males [12,14,32]. There is one report, however, where an increase in cortisol concentrations was observed following resistance exercise [26].…”
mentioning
confidence: 89%